Mechanical ventilatory assistance may reduce dyspnea during walking especially in patients with impaired cardiopulmonary function early after cardiovascular surgery. Issue 6 (June 2016) - Kamisaka, Kenta; Sakui, Daisuke; Hagiwara, Yuta; Kamiya, Kuniyasu; Adachi, Takuji; Iida, Jun; Morishima, Manabu; Ueyama, Koji; Yamada, Sumio
Abstract: Background: To determine which patients effectively respond to ventilatory assistance (VA) and to examine the factors influencing patient response in patients who underwent cardiovascular (CV) surgery. Methods: We conducted the first walking session after surgery either with or without VA in a randomized order. The patients walked with 3 cmH2 O of inspiratory pressure support. We measured dyspnea and leg fatigue during initial walking either with or without VA by using a modified Borg scale. Ventilatory parameters were measured by mechanical ventilation before and immediately after walking. Lung function and maximal inspiratory pressure (MIP) were measured and chest radiographs were analyzed by the same cardiac surgeon on the same day as walking. Results: From the total of 74 patients who underwent CV surgery, 56 patients were successively enrolled in the study. Thirty-five out of 56 patients had dyspnea and 18 patients (30% of the total patients) effectively responded to VA (responders). Minute ventilation/estimated maximum voluntary ventilation immediately after walking significantly decreased with VA, and MIP was lower in responders than in non-responders after surgery. The responders revealed greater pulmonary edema scores than non-responders. Conclusions: The findings of the present study suggest that VA may possibly facilitate successful mobilization early after CV surgery, especially in patients with impaired cardiopulmonary function.